2017
DOI: 10.1007/s00590-017-2039-0
|View full text |Cite
|
Sign up to set email alerts
|

Case report of Kummell’s disease with delayed onset myelopathy and the literature review

Abstract: It is necessary to have a complete knowledge of the clinical, pathological and radiological characteristics of Kummell's disease, so as to follow a correct diagnostic course enabling to prepare the most suitable therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…MRI imaging can find limited fluid filling in the vertebral body. So Kümmell's disease is also referred to as delayed posttraumatic vertebral collapse disease, nonunion of vertebral fractures, and vertebral ischemic necrosis [1,2,18]. Previous studies have suggested that IVC is mainly located in the thoracolumbar region [4,19], which is similar to the segmental distribution of the two groups of patients in this study.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…MRI imaging can find limited fluid filling in the vertebral body. So Kümmell's disease is also referred to as delayed posttraumatic vertebral collapse disease, nonunion of vertebral fractures, and vertebral ischemic necrosis [1,2,18]. Previous studies have suggested that IVC is mainly located in the thoracolumbar region [4,19], which is similar to the segmental distribution of the two groups of patients in this study.…”
Section: Discussionsupporting
confidence: 72%
“…Kümmell's disease is a special type of osteoporotic vertebral compression fracture (OVCF), which is relatively rare in clinical practice [1]. Kümmell's disease is also known as nonunion after OVCF, delayed vertebral osteonecrosis after trauma, and delayed vertebral collapse [2,3]. Imaging examination can discover the late-onset collapse of vertebrae and characteristic change of intravertebral vacuum cleft (IVC), which is considered one of important inducing factors for injured vertebral progress after the collapse, deformity of kyphosis, intractable back pain and spinal cord damage after OVCF [4].…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] But the vertebral body in stage III is incomplete due to posterior cortex collapse, and greater risk of cement leakage in vertebral canal exists during surgery, therefore open surgery is recommended. 33,34 At present, PVP and PKP have become one of the most effective methods to treat vertebral tumors and OVCF 35,36 (including Kümmell's disease).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of KD is usually manifested as intractable lumbago and back pain, and in severe cases, nerve damage may occur [18,19]. X-ray and CT examination shows IVC in the vertebral body, and MRI suggests limited fluid filling in the vertebral body [1,2,20]. IVC is mainly located in the thoracolumbar region, and most of the fractures are wedge-shaped fractures, with fractures occurring near the upper and lower endplates of the vertebral body [11,21].…”
Section: Discussionmentioning
confidence: 99%